Generation Z’s Intention to Use Furniture Waste Briquettes: Insights into Green Energy Awareness and Consumer Willingness to Pay - Andreansyah Saputra; Catur Sugiarto; Mafruhah Izza (Universitas Tidar, 2025)
Renewable energy sources are a key development focus and a strategic project worldwide, given the limitations of non-renewable resources. This has led to the push for the development of new renewable resources. Briquettes are one such alternative resource that is environmentally friendly. Briquettes can replace coal, natural gas, and wood charcoal, thus reducing dependence on non- renewable and environmentally harmful resources. Generation Z, as the younger generation, should consider using briquettes as a fuel source in their daily activities. This study aims to analyze Generation Z's interest in using briquettes and to understand the Segmentation, Targeting, and Positioning of briquettes. The research uses a mixed-method approach with 7 qualitative respondents and 100 quantitative respondents. The findings show that Environmental Awareness, Willingness to Pay, and Product Quality positively influence Generation Z's interest in using furniture waste briquettes. In terms of positioning, briquettes are primary used by Generation Z for various activities during specific moments.